Metacognitive Awareness: Shaping Students’ Speaking Performance in the Hospitality Setting - M Bambang Purwanto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explore the role of metacognitive awareness in improving the speaking performance of hospitality vocational students. Using a mixed-methods design, this study involved 50 students of the Prasetiya Mandiri Polytechnic and combined quantitative data from the adapted Metacognitive Awareness Inventory (MAI) as well as role-play-based speaking tests, with qualitative data from in-depth interviews. The results of correlation analysis showed a significant positive relationship (r = 0.65) between metacognitive scores and speaking performance. The most dominant metacognitive strategies reported by students included self-monitoring during speaking and post-task reflection. These findings reveal that students with high metacognitive awareness tend to be able to manage their communication more effectively in professional situations. Research implications include the importance of integrating metacognitive training in vocational curricula, such as through reflective journals and communication strategy guides. The study also highlights a curriculum gap, where only 32% of respondents reported having received explicit training related to metacognitive strategies. Limitations include small sample sizes, so it is recommended that follow-up studies be conducted longitudinally and across institutions.